EXPERIENCE OF THE RUSSIAN PRE-REVOLUTIONARY FORESTRY LEGISLATION ON PROTECTING STATE AND PRIVATE FORESTS AGAINST FIRES - A. Puryaeva (Russian Journal of Economics and Law)
The article shows measures of forest protection against fires contained in the Russian pr-revolutionary forestry legislation. The author finds it useful to look at the history of the Russian forestry laws, as, in spite of development of high technologies, Russia has suffered tragic consequences of fires in XXI c and was not able to extinguish fires timely.